A case control study of age related macular degeneration and use of statins. Issue 9 (19th August 2005) - Smeeth, L; Cook, C; Chakravarthy, U; Hubbard, R; Fletcher, A E
Abstract : Aims: Age related macular degeneration (AMD) is the leading cause of blindness in industrialised countries. Previous studies have suggested that statins may have a protective effect against the disease; however, existing studies have had limited power to reliably detect or exclude an effect and have produced conflicting results. The authors assessed the risk of AMD associated with the use of statins. Methods: Population based case control study using the United Kingdom General Practice Research Database. 18 007 people with diagnosed AMD were compared with 86 169 controls matched on age, sex, and general practice. The primary outcome was the odds ratio for the association between exposure to statins and AMD. Results: The crude odds ratio for the association between any recorded exposure to statins and AMD was 1.32 (95% CI 1.17 to 1.48), but this reduced to 0.93 (95% CI 0.81 to 1.07, p = 0.33) after adjustment for consultation rate, smoking, alcohol intake, body mass index, atherosclerotic disease, hyperlipidaemia, heart failure, diabetes mellitus, hypertension, use of other cardiovascular drugs, and use of fibrates. There was no evidence that the risk varied by dose of statin, duration of use, or that the risk varied for individual statins. Conclusion: In the short and medium term statin use is not associated with a decreased risk of AMD. Whether subgroups of patients with specific forms of AMD (particularly choroidal neovascularisation) benefit from statin therapy remains a possibility.